Analysis of multidrug-resistance tuberculosis distribution in Indonesia 2021–2023 - Aavinia Kapugu; Fima Lanra Fredrik Gerarld Langi; Angela Fitriani Clementine Kalesaran (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Multidrug-resistant tuberculosis (MDR-TB) is a major obstacle to tuberculosis eradication worldwide. MDR-TB cases are a form of tuberculosis resistant to two main drugs, isoniazid and rifampin. Purpose: To (1) determine trends in the pattern of changes in the number of MDR-TB cases, (2) identify the distribution of MDR-TB cases in Indonesia by time and region (province), and (3) identify clusters based on incidence rates and population density. Method: An observational ecological study using aggregate provincial-level data. MDR-TB case data was obtained from the Indonesian Ministry of Health for 2021–2023. The analysis was conducted descriptively, spatially, and cluster-wise. The spatial epidemiology approach included the creation of thematic maps (choropleth maps), temporal trend analysis, Standardized Incidence Ratio (SIR), and hierarchical cluster analysis using the Ward method. Results: There was an increase in MDR-TB cases in almost all provinces during 2021–2023. After adjusting for population (rate), the provinces with the highest risk were DKI Jakarta, North Maluku, Gorontalo, and North Sulawesi. Spatial analysis showed significant hotspots in West Java and Banten, while other provinces were classified as low risk. Based on clusters, DKI Jakarta formed a separate cluster with the highest rate and density. The distribution of MDR-TB in Indonesia is uneven, with an increase in national cases and concentration of risk in several regions. Conclusion: A spatial-based approach is essential for planning more targeted interventions. These findings indicate that the distribution of MDR-TB in Indonesia is uneven, with an increase in national cases and concentration of risk in certain provinces, so these areas need to be prioritized in MDR-TB control.